2015
DOI: 10.1002/ccd.26106
|View full text |Cite
|
Sign up to set email alerts
|

One‐year results of the ICON (ionic versus non‐ionic contrast to obviate worsening nephropathy after angioplasty in chronic renal failure patients) Study

Abstract: The use of ionic LOCM ioxaglate was associated with a numerically lower mortality at 1 year as compared to iodixanol in patients who underwent cardiac catheterization. Future studies evaluating long-term safety following exposure to different types of CM are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…However, our results indicated that use of NAC showed no protective effect of CI-AKI in diabetic patients, which were similar with other studies [33, 34]. A recent study showed ionic LOCM ioxaglate was associated with a numerically lower one-year mortality than iodixanol in patients with cardiac catheterization [35], which were inconsistent with our results. Therefore, future studies evaluating long-term safety following exposure to different types of contrast media in diabetic patients are warranted.…”
Section: Discussioncontrasting
confidence: 68%
“…However, our results indicated that use of NAC showed no protective effect of CI-AKI in diabetic patients, which were similar with other studies [33, 34]. A recent study showed ionic LOCM ioxaglate was associated with a numerically lower one-year mortality than iodixanol in patients with cardiac catheterization [35], which were inconsistent with our results. Therefore, future studies evaluating long-term safety following exposure to different types of contrast media in diabetic patients are warranted.…”
Section: Discussioncontrasting
confidence: 68%
“…The study was a relatively small randomized controlled trial and underpowered for AKI. The present paper in Catheterization and Cardiovascular Interventions by Giustino et al examines the 30‐day and one year results of the ICON trial with respect to renal failure and mortality . There were no differences in renal outcomes and a numerically (but not statistically significant) higher rate of death at one year in the iodixanol group versus the group ioxaglate (9.1% vs. 2.7%, P = 0.07).…”
mentioning
confidence: 82%
“…Of the works found, four countries contributed to the studies: two from the United States (18,20) , one from Brazil (19) , one from Turkey (21) and one from Japan (22) . All articles present were in English.…”
Section: Countriesmentioning
confidence: 99%
“…Only one study outlined the clinical and sociodemographic profile of patients who developed CIN (18) ; however, CIN incidence varied between 6% to 24% (18)(19)(20)(21)(22) . It was observed that the study samples vary from 135 to 2552 people (18)(19)(20)(21)(22) . Analyzing the publications that make up this review, it can be seen that, in general, there was a difference in renal involvement according to the social indicators of sex and age.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation